PENGARUH LINGKUNGAN KERJA DAN STRES KERJA TERHADAP MOTIVASI KERJA PEGAWAI KANTOR CAMAT KUTA COT GLIE KABUPATEN ACEH BESAR - Muhammad Ridwan; Yahya Kobat; Laila Maisarah (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2023)
The purpose of this study was to analyze the influence of the work environment and work stress on employee motivation. The problem that arises is whether the work environment and work stress affect the work motivation of employees at the Kuta Cot Glie District Office, Aceh Besar District? The research design is a survey. This type of research is quantitative. The research sample is 29 respondents. the analysis shows that simultaneously there is a positive influence between the work environment and work stress on work motivation of 0.778 or 77.8%. After the F test was carried out, the Fcount (20,760) > Ftable (3,354) was obtained, which means it was significant. The partial test results show that the work environment has a positive effect on work motivation with a value of 0.697 or 69.1%. Work stress has a negative effect on work motivation with a value of -0.090 or -09.0%.